Digital Da’wah and Authority Contestation in Indonesia: Between Traditional Ulama and Modern Influencers - Wahyu Khoiruz Zaman; Ilyas Supena; Muhammad Sulthon; Muh. Amirudin (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This study explores the contestation of religious authority in Indonesian digital da’wah, examining how traditional ulama and Muslim influencers interact and negotiate their legitimacy on social media platforms such as YouTube, Instagram, and TikTok. Utilizing a qualitative digital discourse analysis combined with non-participatory online observation, the research analyzes selected religious content to understand communication styles, symbols of authority, audience engagement, and narratives of legitimacy. The findings reveal that the rise of Muslim influencers and digital preachers has led to a fragmentation of religious authority, shifting from traditional sources such as scholarly lineage and institutional affiliation to factors like visibility, popularity, affective communication, and algorithmic circulation. This transformation creates opportunities for democratizing Islamic preaching, making it more accessible to younger Muslims, but also introduces risks such as superficial religious understanding, pseudo-authority, and polarization. Traditional ulama respond by adopting integrative, collaborative, and defensive strategies, often involving younger digital actors to adapt classical messages into platform-friendly formats. The results highlight the complex dynamics of digital religious authority, emphasizing the importance of understanding how authority is reshaped through interactions between tradition, platform logic, and digital visibility, which has significant implications for the future of Islamic discourse in Indonesia. This article contributes to Islamic studies by showing that religious authority in the digital age is not simply displaced, but contested, negotiated, and reconfigured through the interaction between scholarly tradition, platform logic, generational mediation, and digital visibility.